Recovery of shallow charge-trapping defects in CsPbX3 nanocrystals through specific binding and encapsulation with amino-functionalized silanes - González-Pedro, Victoria (2020)
We report a facile methodology to restore photoluminescence (PL) of CsPbBr3 nanocrystals (NCs) based on their postsynthetic modification with 3-aminopropyltriethoxysilane (APTES). By this methodology, a stark PL recovery factor of near 2-fold was obtained compared to their uncoated counterparts. 1H NMR studies confirmed the presence of APTES on the NCs shell and provided more insight into the nature of the alkoxysilane passivation mechanisms. We further highlight that, contrary to expectations, preferential attachment of APTES does not take place through their amine terminal groups. The proposed surface-repair strategy can be extended to other halide compositions, yielding similarly effective 4-fold and 2-fold PL enhancements for CsPbCl3 and CsPbI3 NCs, respectively. Our work thus exemplifies that careful management of the perovskite NC interfaces and surface engineering is one of the most important frontiers in this emerging class of optoelectronic materials.